Advances in library administration and organization. Vol. 29 - Williams, Delmus Eugene; Golden, Janine (Emerald, 2010)
"The Advances in Library Administration and Organization Series provides a body of research literature that contributes to the base of organizational theory upon which library administrators rely. Its mix of contributions to the literature of library administration and organization is both diverse and eclectic. This volume of the series covers a variety of topics relating to the management of academic, public and school libraries."
Keywords: Library administration.; elektronické knihy; electronic books